Design Of Linear Polarization Antenna For Wireless Mimo Application - Abd. Aziz, Mohamad Zoinol Abidin; Abd Rashid, Kamarul Ariffin; Husain, Mohd Nor; Othman, Abdul Rani; Saad, Muhammad Majdi; Senon, Misida; Ahmad, Mohamad Tarmizy; Hamidon, J. S. (Asian Research Publishing Network (ARPN), 2014)

(untitled)
This paper presents the design of the linear polarized antenna for wireless MIMO communication system.It is impossible to fulfill the demand of the wireless communication system due to limitations in channel capacity on single input single output (SISO) systems. Multiple input multiple output (MIMO) system has become a famous research field for the next generation wireless communication system in order to overcome this problem. Since polarization diversity is effective to avoid the fading loss caused by multipath effects, therefore, polarization diversity becomes one of the most important techniques that can be used to enhance MIMO system performances.It can be utilized to improve the communications channel capacity and utilize the frequency spectrum with frequency reuse technique.Therefore,the development of linear polarized antenna is significant in order to improve the wireless MIMO system performance based on polarization diversity technique.Polarization diversity can be utilized to double the frequency spectrum to realize frequency reuse and improve the communications capacity.This project is to design an antenna that can provide linear polarization to reduce the signal losses.